Physical properties, antioxidant activity, and preference level of snack bars made from a composite flour of sorghum, mung bean, and purple yam : Sifat fisik, aktivitas antioksidan dan tingkat kesukaan snack bar berbahan baku tepung komposit sorgum, kacang hijau dan uwi ungu - Kusumaningrum, Anggitya Elsyafitri; Tamaroh , Siti; Fitri, Ichlasia Ainul (JITIPARI, 2025)
Purple yam is one of the tubers that serves as a source of antioxidants but has not been optimally utilized. Therefore, it needs to be diversified by processing it into snack bars. This study aims to develop snack bars made from purple yam flour, sorghum flour, and mung bean flour, which have the potential to serve as antioxidant sources and are preferred by panelists. In this study, snack bars were prepared using composite flour (sorghum:mung bean) and purple yam flour in varying ratios: 95:5, 90:10, 85:15 for the composite flour and 20%, 30%, and 40% for the purple yam flour. The snack bars were evaluated for color, texture, moisture content, antioxidant activity, and preference level. Selected samples were further analyzed for ash content, protein content, fat content, anthocyanin content, and crude fiber content. The experimental design used was a Completely Randomized Design (CRD) with two factors. The snack bars with a composite flour ratio (sorghum:mung bean) of 85:15 and 30% purple yam flour were identified as the best treatment, preferred by panelists and exhibite high antioxidant activity. These snack bars had a moisture content of 13.40%, ash content of 8.83% (db), protein content of 19.75% (db), fat content of 8.80% (db), crude fiber content of 9.54% (db), antioxidant activity of 68.02% (RSA), and anthocyanin content of 37.40 mg/100g